Russell on meaning and denotation: The argument of 'On Denoting' - de, Almeida Claudio (My University, 1992)
The aim of the thesis is twofold. Firstly, it is argued (1) that Frege's theory of meaning ('Sinn') and denotation ('Bedeutung') is the first successful non-psychologistic response to what has been called 'the puzzle of identity' and (2) that, where Frege's theory differs most significantly from the theory of meaning and denotation developed by Russell in The Principles of Mathematics and in his unpublished manuscripts on logic of 1903-1905, Russell was right. Secondly, it is shown that Russell was again right when he claimed that the central argument of 'On Denoting' completely discredits both his own and Frege's theory of meaning and denotation. An interpretation of the relevant passage of 'On Denoting' is put forward. The discussion makes evident that it is virtually impossible to disentangle that argument if one ignores his unpublished work on the topic.
Keywords: Philosophy; Philosophy